FORMULATION AND EVALUATION OF TOPICAL TRANSFEROSOMES LOADED LIDOCAINE FOR TOPICAL DELIVERY FOR BURNS, IN VITRO CHARACTERIZATION AND IN VIVO STUDY - NOORI, SARMAD DHEYAA; ALI, SAMER KHALID; MUDHAFAR, MUSTAFA; ALSAILAWI, HASAN ALI; KASSEM, AMIRA B. (International Journal of Applied Pharmaceutics, 2025)
Objective: The current investigation aimed for loading Lidocaine (LID), a local anesthetic agent, into transferosomes topically. Lidocaine has substantial first-pass metabolism results in low oral bioavailability. In order to prevent oral complications, the production of LID transferosomes was to improve LID topical distribution. Methods: By using a 21.31 factorial design and different amounts lipids and surfactants, transferosomes formulas were created. LID transferosomes were constructed applying ethanol injection method. LID transferosomes were evaluated with regard to entrapment efficiency percent (EE%), particle size (PS), polydispersity index (PDI), and zeta potential (ZP). Extra experiments were conducted on the optimum formula. Results: Utilizing Design Expert®, the optimum formula (F2) was evaluated, revealing EE% of 90.25±1.23%, PS of 194.50±6.50 nm, PDI of 0.602±0.0005, ZP of 50.45±1.15 mV, and amount of drug release after 6 h (Q6h) of 45.00±1.50. Further, the optimum transferosomes showed vesicles without aggregation under transmission electron microscope evaluation. In vitro release study showed that the optimum formula was released in sustained manner than LID solution. In addition, during storage, the optimum formula was stable. The histological investigation verified the safety of the optimum transferosomes. Conclusion: The results confirmed the ability to utilize LID transferosomes for burn treatment topically.